THE RELATIONSHIP BETWEEN APOB AND APOA1 WITH INSULINEMIC STATUS IN PREDIABETIC SUBJECTS (Bioresearch Communications, 2022)
The present study was mainly aimed at exploring the causal association of the atherogenic (ApoB) and antiatherogenic apolipoproteins (ApoA1) and their ratio in the basic defects of pancreatic β cell dysfunction and insulin resistance in type 2 Diabetes Mellitus (T2DM). An intermediate stage towards diabetes, the prediabetic stage, was chosen to explore the association. Following a standardized selection process, 131 subjects were purposefully recruited for the study, including 18 with impaired fasting glucose (IFG), 56 with impaired glucose tolerance (IGT), and 57 with type 2 diabetes (T2DM). Fifty-nine healthy subjects served as controls. Glucose, lipid and insulin were estimated by glucose-oxidase, enzymatic colorimetric assay and enzyme linked immunosorbent assay (ELISA) respectively. Serum ApoB and ApoA1 were estimated by immuno-nephelometric method. Appropriate statistical tools were used to calculate statistical differences using Statistical Package for Social studies (SPSS) for Windows V12. Absolute insulin (mIU) levels were significantly higher in the IGT and T2DM groups compared to controls (p 0.001 and p = 0.001, respectively). HOMA%B (meanSD) was significantly lower in T2DM groups (p=